(untitled) (Bangladesh Journal of Medical Microbiology, 2023)
Necrotizing pneumonia (NP) is an uncommon severe complication of pneumonia in children. It is characterized by destruction of the underlying lung parenchyma resulting in multiple small, thin-walled cavities and is often accompanied by empyema and bronchopleural fistulae. Early consultation with thoracic Surgeon can be life-saving. We report a case of a child with NP in whom no pathogen is documented in its aetiopathogenesis. Severe pneumonia, which shows slow response to recommended antibiotics treatment, should raise the suspicion of NP and possibly one of the polymicrobial origins. Even in resource‑constrained settings, prompt institution of antibiotics and supportive care can result in resolution of pulmonary lesions. Bangladesh Journal of Medical Microbiology, January 2022;16(1):31-35